Isolation and selection of indigenous chicken-derived Bacillus subtilis strains as potential probiotic alternatives to antibiotics against Gram-negative enteropathogens. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The increasing antibiotic resistance in poultry pathogens presents a significant public health risk, leading to the exploration of effective alternatives in broiler feed, particularly probiotics such as Bacillus subtilis. This study aimed to isolate B. subtilis strains from indigenous chicken feces that can inhibit Escherichia coli and Salmonella typhimurium strains, common causes of diarrhea in poultry. Materials and Methods: Bacillus strains were isolated from chicken feces and screened for antibacterial activity using an agar well diffusion assay. Bacillus strains were identified via 16S rRNA gene sequencing. Their probiotic potential was assessed through in vitro assays measuring extracellular enzyme production, adhesion properties, and resilience to acidic and bile salt conditions. Freeze-drying techniques were applied to evaluate strain viability and stability. In vivo studies determined the colonization ability of selected strains in the chicken intestine. Results: From 121 B. subtilis isolates, six B. subtilis strains demonstrated notable antibacterial activity against both E. coli and S. typhimurium. Five strains were confirmed as B. subtilis through sequencing. Based on their probiotic attributes, B. subtilis H1 and B. subtilis BSn5 were identified as the most promising candidates. Notably, B. subtilis BSn5 exhibited stable viability when freeze dried, surviving for up to two months, and successfully colonized the chicken intestinal tract in vivo. Conclusion: These findings indicate that B. subtilis BSn5 may serve as a viable probiotic alternative to antibiotics in poultry, with regular supplementation necessary to sustain its benefits.J. Adv. Vet. Anim. Res., 12(1): 53–63, March 2025http://doi.org/10.5455/javar.2025.l871